Pengaruh Tingkat Pendidikan Dan Pendapatan Kepala Keluarga Terhadap Penyediaan Air Bersih, Sanitasi, Sampah Di Desa Boja Kecamatan Boja Kabupaten Kendal - Putri, Dwi Utami; Tjahjono, Heri; Aji, Ananto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2017)
This study aims to determine the level of formal and non-formal education of the community, to know the magnitude of the expenditure of household allocated for the purposes of environmental management, to know the effect of educational levels and public income on environmental management in Boja Village. Researchers collected data using questionnaires, interviews, and documentation. Data analysis technique used descriptive analysis percentage and multiple regression analysis. The result of the research shows that the level of formal education of Boja Village is still low, while non formal education includes socialization/training related to environmental management has been followed by 49 household. A total of 88 head of household allocated their income for environmental management purposes from Rp 15.000-Rp 60.000. The variable of educational level and income level related to water supply, sanitation, garbage variable is 28,40%, so it is stated enough to have influence. The conclusion of this study is